Determination of three estrogens in environmental water samples using dispersive liquid-liquid microextraction by high-performance liquid chromatography and fluorescence detector - Sousa, Érika M. L. (2020)
In this work the dispersive liquid-liquid microextraction technique (DLLME) is presented as an important alternative to the classical extraction methods and was used to extract and concentrate before estrogen quantification by HPLC in environmental water samples. For the evaluation of the analytical methodology, the following conditions were used: sample volume: 8 mL; extraction solvent: 200 μL of chlorobenzene; dispersive solvent: 2000 μL of acetone. The enrichment factor (EF) was 140 for Estrone, 202 for 17β-estradiol (E2) and 199 for 17α-ethinylestradiol (EE2). Limit of detection was 20 ng L-1 for E1, 3.1 ng L-1 for E2, 2.7 ng L-1 for EE2. Repeatability and intermediate reproducibility presented values of relative standard deviation lower than 10%. Finally, recovery tests were performed to evaluate the water matrices effects on the extraction performance, resulting in recoveries between 76% and 110% in surface water and between 84% and 109% in wastewater.